LINEAR CHANNEL’S CHARACTERISTICS OF INFORMATION TRANSMISSION - Щербак, Л. М.; Челкован, В. І. (Science-based technologies, 2009)
Considered is modern point of view of researching the main linear channel’s characteristics of information transmission, including space-time and spectral characteristics. Their physical interpretation is defined.